Simulation of direct sequence spread spectrum and multipath radio channels in W-CDMA system - 369426 Teoh, Jun Cheat (Skudai : Universiti Teknologi Malaysia, 2001)
Project Paper (Bachelor of Electrical Engineering (Telecommunications)) - Universiti Teknologi Malaysia, 2001